PLANKTON ANALYSIS IN THE PONDS OF CATFISH (Clarias sp) AND NILE TILAPIA (Oreochromis niloticus) - Arfiati, Diana; Inayah, Zakiyyah Nur; Lailiyah, Shofiyatul; Dina, Karina Farkha (JFMR (Journal of Fisheries and Marine Research), 2021)
Clarias and Nile tilapia ponds contain high organic matter levels which will be decomposed by bacteria. It also produces carbon dioxide, which can be utilized by phytoplankton for photosynthesis process. This research aimed to compare the types of phytoplankton and zooplankton in Clarias and Nila tilapia ponds for eutrophication and water quality control. The research was conducted in August-September 2020. The water samples were taken using plankton net to become 35 ml from Clarias and Nile tilapia ponds. Analysis of plankton abudance, diversity, Evenness and Dominance Index was carried out in the Laboratorium Hidrobiologi. The analysis result of the average abundance of phytoplankton in the Clarias ponds was 71.026 cell/mL (11 genera), and zooplankton was 93 ind/mL (4 genera). Meanwhile in Nile tilapia ponds was 1.503 cell/mL (9 genera), and zooplankton was 91 ind/mL (1 genus). The average of zooplankton in Nile tilapia pond was higher than in catfish ponds; since Clarias are carnivores while Tilapia are omnivores. The plankton diversity index of catfish pond was average 0.817, while in Nile Tilapia was average 0.553. The evenness ndex of catfish pond was average 0.5, while in Nile Tilapia was average 0,4. The dominance index of catfish pond was average 0.59, while in Nile Tilapia was average 0.77. The conclusion obtained is the type of phytoplankton in Catfish pond consisted of 11 genera (99.62%) and zooplankton of 4 genera (0.38%), while in Nile Tilapia pond the type of phytoplankton consisted of 9 genera (97.85%) and zooplankton of 1 genera (2.15%).